CircVAMP3 promotes acute lung injury progression by regulating the miR-580-3p/STING/IFN-β axis in macrophages - Zheng Zhou; Shuyang Chen; Yajun Wang; Shujing Chen; Jinjun Jiang (PeerJ)
Circular RNA (circRNA) is a prominent group of non-coding RNA (ncRNA) that regulates gene expression at the post-transcriptional level in various diseases including acute respiratory distress syndrome (ARDS). In our study, circVAMP3 was a novel circRNA significantly increased in macrophages in an acute lung injury (ALI) model. Through knockdown and overexpression of circVAMP3, we found circVAMP3 promoted the expression of IFN-β in macrophages, which was vital in the pathophysiological process of ARDS. Moreover, we showed that circVAMP3 targeted Stimulator of Interferon Genes (STING) through miR-580-3p by bioinformatics analysis and intervene of miR-580-3p. CircVAMP3 acts as a pro-inflammation ncRNA by regulating the miR-580-3p/STING/IFN-β axis and could be a potential biomarker and therapeutic target for ARDS.